Citizens’ Political Responsibility and Collective Identity: A Spinozistic Answer to Jaspers’s Question on Guilt (2019)
The question on guilt that Jaspers poses to the Germans was not only valid after the Holocaust, it can be raised to other peoples who must answer for the crimes committed by the state which act on behalf of the people that gave support to them. In this paper, I elaborate a notion of citizens’ political responsibility in order to argue to what extent—and under what circumstances—the citizens of a political community must respond for the deeds of the political institutions that govern them. For that purpose, I try to explain Spinoza’s notion of political authority in relation to Jaspers’ notion of political guilt. This Spinozistic approach has the advantage of freeing us from moral guilt—a misleading notion in political arena as I will argue—but it demands from us a genuine self-reflective and therapeutic procedure that if applied to politics would reveal a different path from Jaspers’ guilt. The aim of this therapeutic is to bring about a profound change in the personal and political identity of both citizen and political community. © 2019, Springer Nature B.V.